NUMBER OF FRIENDS IN SCHOOL AND THE LEVEL OF SELF-CONFIDENCE OF THE STUDENTS - Jerald, Moneva; Honey Me, Villegas (International Journal of Research -GRANTHAALAYAH, 2020)
Friendship is extremely important in people’s lives. On the other hand, self-confidence is some of the important variable for the students. Those who have high level of self-confidence tend to have positive outlook on his capacities. This study aims to assess the relationship between the number of friends in school and the level of self-confidence of the students in Jagobiao National High School-Senior High Department. The researcher used a descriptive quantitative design that seeks descriptive information on the relationship between the students’ number of friends and their level of self-confidence and also; there are two hundred forty-three respondents. The instrument used for the data collection was a quantitative survey using Likert scale to gather the needed data the researcher adopted a questionnaire from Rosenberg (1965). The data was analyzed through use of weighted mean and chi-square for determining the significant association between the number of friends in school and the level of self-confidence of the students. The findings of the study showed that there was no significant association between the number of friends in school and the level of self-confidence of the students. Generally, having a low or high number of friends does not seem to affect the student's self-confidence.